Tracing the historical and ideological roots of ISIS: Shi’ite or Sunni? - Makrum Makrum (IAIN Salatiga, 2016)
This article describes a comprehensive study of ISIS (the Islamic States of Iraq and Syiria) by examining both their historical and ideological roots, Shi’ite or Sunni – including their patterns and terror motives and also by mapping their doctrinal understanding that they adopt. The data stem from various studies, books and news that are widely spread in mass media by literature study (library research). This study was inspired by the emergence of ISIS which in recent years has shocked the world for their savagery and ferocity in committing the murder. Moreover, their leader (Abu Bakr al-Baghdadi) has declared himself as the caliph and called on Muslims worldwide to join them. That issue has been a controversy across the Muslim world; many Muslim groups accepted and joined the ISIS, while others rejected its presence. Based on these library research results, it can be inferred that, historically ISIS has existed since 2004 and the origin of ISIS cannot be separated from the existence of Tawhid wa alJihad. In terms of doctrine, the concept of shared leadership of ISIS tends to lead to Sunnis, although al-Baghdadi himself does not meet the criteria to be appointed as caliph. Personally, al-Baghdadi does not posses the leadership capacity required as a caliph, based on one of the caliph’s criteria, that is ‘adalah (justice) that he does not have. Artikel ini, dengan menggunakan pendekatan kualitatif, mengkaji akar sejarah dan ideologi ISIS, Syi’ah atau Sunni –termasuk di dalamnya pola dan motif teror–, kemudian memetakan paham doktrinal yang mereka anut agar diperoleh kajian yang komprehensif tentang ISIS. Data diperoleh dari studi kepustakaan (library research) yang berasal dari berbagai hasil penelitian, buku, dan berita-berita di media massa. Penulisannya terinspirasi oleh kemunculan ISIS yang pada beberapa tahun terakhir telah menghebohkan masyarakat dunia, karena kebiadaban dan keganasannya dalam melakukan pembunuhan. Selain dari itu, Abu Bakar al-Baghdadi sebagai pemimpin ISIS, mengangkat dirinya sebagai khalifah dan menyeru umat Islam di seluruh dunia untuk bergabung ke dalam kelompoknya.Deklarasi yang sepihak itu mendapatkan respons beragam. Sebagian kaum muslimin memilih menjadi anggota ISIS, sedangkan yang lain menolak kehadirannya, karena ISIS dinilai melakukan kekerasan hingga menjurus kepada pembunuhan. Berdasarkan hasil penelitian ini, secara historis ISIS sudah ada sejak tahun 2004 dan asal muasal ISIS tidak terlepas dari keberadaan Tauhid wa al-Jihad. Dilihat dari segi doktrinal, konsep kepemimpinan yang dianut ISIS cenderung mengarah ke Sunni, meskipun al-Baghdadi sendiri tidak memenuhi kriteria untuk diangkat menjadi khalifah. Secara personal, kapasitas al-Baghdadi sebagai pemimpin, belum dapat terpenuhi secara sempurna, karena unsur ‘adalah (adil) yang semestinya ada dalam diri seorang pemimpin, tidak ia miliki.